Subacute Limb Ischemia Induces Skeletal Muscle Injury in Genetically Susceptible Mice Independent of Vascular Density - McClung, Joseph M. (J Vasc Surg, 2015)
OBJECTIVE: The primary preclinical model of peripheral artery disease (PAD), which involves acute limb ischemia (ALI), can result in appreciable muscle injury that is attributed to the acuity of the ischemic injury. A less acute model of murine limb ischemia using ameroid constrictors (AC) has been developed in an attempt to mimic the chronic nature of human disease. However, there is currently little understanding of how genetics influence muscle injury following subacute arterial occlusion in the mouse. METHODS: We investigated the influence of mouse genetics on skeletal muscle tissue survival, blood flow, and vascular density by subjecting two different mouse strains, C57BL/6 (BL6) and BALB/c, to ALI or subacute limb ischemia (SLI) using single (1AC) or double (2AC) ameroid constrictor placement on the femoral artery. RESULTS: Similar to ALI, the 2AC model resulted in significant tissue necrosis and limb perfusion deficits in genetically susceptible BALB/c but not BL6 mice. In the 1AC model, no outward evidence of tissue necrosis was observed, and there were no differences in limb blood flow between BL6 and BALB/c. However, BALB/c mice displayed significantly greater muscle injury, as evidenced by increased inflammation and myofiber atrophy, despite having no differences in CD31(+) and SMA(+) vascular density and area. BALB/c mice also displayed significantly greater centralized myonuclei, indicating increased muscle regeneration. CONCLUSIONS: The susceptibility of skeletal muscle to ischemia-induced injury is at least partly independent of muscle blood flow and vascular density, consistent with a muscle cell autonomous response that is genetically determined. Further development of preclinical models of PAD that more accurately reflect the nature of the human disease may allow more accurate identification of genetic targets for therapeutic intervention.